Multiband in-band full-duplexing using fractal concentric circular antenna arrays - Geili Elsanousi; Mohammed Abbas; Franz Hirtenfelder; Raed AbdAlhameed; Xin-She Yang; Tuan Le; Huan X. Nguyen (EURASIP Journal on Wireless Communications and Networking, 2024)
Abstract In this work, we present an innovative approach to enhance multiband communication systems by enabling the antenna subsystems to simultaneously transmit and receive across multiple independent in-band full-duplex (IBFD) channels, i.e. multiband-IBFD (MIBFD). This capability is powered by fractal antenna arrays, specifically using hexagonal star array (HSA) geometry. The approach provides a unique self-interference cancellation (SIC) capability across multiple bands (MB-SIC), achieved through translation or rotational transformations of self-similar or self-affine array structures. Simulation results demonstrate significantly enhanced SIC bandwidth for three signals at sub-frequencies near 5 GHz, with the integration of subbands’ SIC bandwidths achieving 1.4 GHz across these subbands. Further enhancements include combining this method with a technique involving the elevation of the central receiving element, significantly broadening the SIC bandwidth compared to traditional methods. Additionally, the multiband functionality is validated with pilot signals at 2.68 and 5.2 GHz, showing effective SIC in these narrow bands. This research presents a promising path for optimising radio resources in multiband communication systems.